Comparison of the Effects of Fixed and Removable Functional Orthodontic Treatment on the Mandibular Trabecular Bone in Fractal Analysis - Nurver Karslı; Can Arslan; Derya Germeç Çakan; Ayşe Tuba Altuğ; Senem Tuğra Dönmez; Asya Atasoy Yücesan (Turkish Journal of Orthodontics)
Objective: The aim of this retrospective study was to compare the effects of the Twin block and Herbst appliances on the mandibular trabecular pattern using fractal dimension analysis (FDA) of panoramic radiographs (PRs). Methods: The PRs of 50 subjects with skeletal Class II malocclusion who underwent the Twin block (T-group, average age: 11.63±0.87; 25 girls, 25 boys), 50 subjects with skeletal Class II malocclusion who underwent the Herbst (H-group, average age: 11.72±0.91; 27 girls, 23 boys), and 50 controls (C-group average age: 11.67±0.83; 24 girls, 26 boys) were selected. The condyle, corpus, and angulus regions of all groups in the mandible were examined using FDA. Results: The condylar region (p≤0.001) and corpus mandible in the treatment groups (T-group: right, p≤0.05, left, p≤0.01; H-group: p≤0.05), as well as the left and right condylar region (p≤0.001) and left corpus mandible (p≤0.05) in the C-group, all indicated substantial increases in FDA between T0 and T1. Inter-group comparisons indicated that the T-group had greater variances in the condyle (p≤0.001) compared to the H group. Conclusion: As the findings revealed both Twin block and Herbst appliances not only contributed to the dentoalveolar structure but also provided remodeling of the mandibular trabecular structure. Consequently, the null hypothesis was rejected.